Minimizing oil uptake in lotus root chips: leveraging hydrocolloids for improved quality - M, Kamalish; Gayathri, G (Journal of Postharvest Technology, 2023)
The present study was aimed to assess the influence of hydrocolloids (pectin and gelatin) to reduce the oil absorption in fried lotus root chips. Lotus root was hand peeled and sliced into 0.2 cm thickness. Then blanched in calcium chloride 0.5g/100ml water at 850C for 30 seconds followed by immersion in different concentration of gelatin and of pectin in 100ml of water at 370C for 2 minutes. The coated chips were fried at 1800C in groundnut oil till the surface becomes golden brown. The lotus root chips prepared using different concentration of pectin and gelatin coating was evaluated for its moisture, lipid and texture profile. The moisture content increased with increase in pectin and gelatin concentration. Pectin and gelatin significantly reduced the oil absorption with increase in concentration. Lotus root chips prepared using 1g of pectin/ 100ml of water was rated (8.24) most acceptable by semi-trained panel members on a nine-point hedonic scale. The hardness of the treated chips ranged between 832.463±74.54 to 845.541±78.45. the colour analysis L*, a* and b* ranged from 48.48±5.80 to 46.81±0.33, 1.29±0.52 to 1.43±0.53 and 15.25±1.44 to 12.98±3.43 respectively. Pectin and gelatin can be used to reduce the oil absorption in fried products